Extraction of classification rules from socio-demographics and biochemistry datasets of schizophrenia patients using multi-objective genetic algorithms - Kaya, Buket; Turkoglu, Ibrahim (My University, 2013)
This paper presents a method for extracting automatically classification rules via multi-objective genetic algorithms. The paper also proposes a novel objective measure to quantify the similarity of the rules. The other objectives of the rules are average support value and accuracy. We experimentally evaluate our approach on socio-demographics and biochemistry datasets of schizophrenia patients and demonstrate that our algorithm encourages us to improve and apply this strategy in many real-world applications. © 2013 IEEE.
2013 IEEE 7th International Conference on Intelligent Data Acquisition and Advanced Computing Systems, IDAACS 2013 -- 12 September 2013 through 14 September 2013 -- Berlin -- 101988
Keywords: classification rules; data mining; multi-objective genetic algorithms; schizophrenia patients